Polyurethane with high frequency, high damping and low compression set and method of making and use thereof
Patent Information
- Application Number
- CN202511955450.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-12-23
AI Technical Summary
[0004]本发明提出一种高频高阻尼低压缩永久变形的聚氨酯及其制备方法和用途,解决了现有技术中聚氨酯阻尼性能差和抵抗压缩永久变形的能力无法同时有效提升的问题
1、本发明中通过引入阻尼剂协同混合异氰酸酯体系,实现了聚氨酯材料高频高阻尼和低压缩永久变形的同步提升,同时还具有一定的阻燃性能,用于制备的铁路用垫板,其减振降噪,抑制钢轨剥磨的效果优异,显著延长了钢轨服役寿命。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyurethane material technology, and relates to high-frequency, high-damping, low-compression-permanent polyurethane, its preparation method, and its applications. Background Technology
[0002] Polyurethane damping materials are widely used in construction, transportation, and other fields due to their excellent vibration reduction and noise reduction performance. Especially in the rail transit industry, their application in key components such as rail pads and vehicle suspension elements plays an irreplaceable role in vibration reduction, noise reduction, and safety improvement. However, as modern transportation vehicles such as high-speed rail develop towards higher speeds, greater loads, and longer service lives, more stringent requirements are placed on the core performance of damping materials: First, the material needs to maintain a high loss factor under wide temperature range and high-frequency vibration conditions, i.e., possess high-frequency, high-damping characteristics to effectively dissipate intense mechanical energy; second, the material needs to have low compressive permanent deformation capacity to ensure the long-term stability of the dimensions and function of vibration damping components, avoiding preload loss and vibration damping failure due to permanent deformation. However, there is often an inherent contradiction between the damping performance and compression set of polyurethane materials: increasing the peak damping and widening the temperature range by increasing the mobility of molecular chain segments usually sacrifices the material's resilience and deformation recovery, leading to increased compression set and decreased durability; conversely, strengthening molecular chain constraints to improve compression set inhibits chain segment movement, resulting in reduced damping performance, especially at high frequencies. For example, Chinese patent application CN 120535721 A discloses a high static stiffness, high damping, low-pressure variable polyurethane elastomer and its preparation method. By introducing bio-based hydrolysis-resistant polyols and branched unit alcohols, the combined effect of these two components significantly enhances the elastomer's damping effect, reduces compression set, effectively improves the product's performance in heavy-haul railway applications, and extends its service life. However, this method only tested the loss factor at 60 Hz and did not examine the damping behavior at higher frequencies. Whether the material is suitable for high-frequency vibration environments, such as high-frequency impacts from rail transit wheels, is unpredictable.
[0003] In summary, current technologies remain limited to improving a single performance dimension. Research exploring the synergistic balance between high-frequency, high-damping and low-compressive-force properties of polyurethane materials is still scarce. This severely restricts the application of polyurethane damping materials in high-end industrial vibration reduction, particularly in rail transit systems where durability and reliability are paramount. Developing a polyurethane material capable of simultaneously achieving high-frequency, high-damping performance and good low-compressive-force capabilities to meet the urgent needs of modern transportation equipment for long-term, reliable vibration reduction, noise reduction, and safety protection is of paramount importance. Summary of the Invention
[0004] This invention proposes a high-frequency, high-damping, low-compression-permanent polyurethane, its preparation method, and its applications, which solves the problem that the damping performance of polyurethane in the prior art cannot be effectively improved at the same time.
[0005] The technical solution of this invention is implemented as follows: Technical Topic 1 The key to this high-frequency, high-damping, low-compression-performance polyurethane lies in its formulation of a polyol component and an isocyanate component in a ratio of 1.05-1.15. Specifically, by mass, the polyol component comprises: 60-80 parts polyether polyol, 15-25 parts chain extender, 15-25 parts damping agent, 3-8 parts nano-montmorillonite, 0.03-0.08 parts catalyst, and 0.5-1.5 parts antioxidant. The isocyanate component is a mixture of 4,4'-diphenylmethane diisocyanate and hexamethylene diisocyanate in a mass ratio of 2.5-3:1. The method for preparing the damping agent includes the following steps: in the presence of an acid-binding agent and a solvent, 4-chloro-3-methylphenol is reacted with dimethyl phosphite to generate a phosphorus-containing aromatic intermediate, which is then subjected to a nucleophilic substitution reaction with 2-chloroethylamine, and the damping agent is obtained after post-treatment; the molar ratio of 4-chloro-3-methylphenol, dimethyl phosphite and 2-chloroethylamine is 8-12:5-10:10-12.
[0006] Preferably, the molar ratio of 4-chloro-3-methylphenol, acid binder, dimethyl phosphite and 2-chloroethylamine is 8-12:5-10:5-10:10-12.
[0007] Preferably, the method for preparing the damping agent includes the following steps: In the presence of a solvent, 4-chloro-3-methylphenol and an acid-binding agent are mixed and kept at 0-5℃ for 18-22 min. Then, dimethyl phosphite is added dropwise. After the addition is complete, the temperature is raised to 50-70℃ and the reaction is carried out for 2.5-3.5 h. Then, 2-chloroethylamine is added to the reaction system, the temperature is raised to 80-90℃, and the reaction is continued for 5-6 h. After the reaction is completed, the damping agent is obtained through post-treatment.
[0008] Preferably, the post-processing steps include: allowing the product to settle, filtering, washing, and drying.
[0009] In this invention, the isocyanate component is a compound system of 4,4'-diphenylmethane diisocyanate (MDI) and hexamethylene diisocyanate (HDI). When MDI and HDI are compounded in a mass ratio of 2.5-3:1, a synergistic effect is produced. The polyurethane network constructed by the two synergistically achieves high damping performance over a wide temperature range. Experiments have shown that the synergistic effect of the two, resulting in low compression set and high damping performance over a wide temperature range, is something that neither MDI nor HDI alone can achieve.
[0010] Preferably, the acid-binding agent is triethylamine.
[0011] Preferably, the molar ratio of 4-chloro-3-methylphenol, triethylamine, dimethyl phosphite, and 2-chloroethylamine is 8-12:5-10:5-10:10-12.
[0012] Preferably, the ratio of 4-chloro-3-methylphenol to solvent is 1g:8-12ml.
[0013] Preferably, the acid-binding agent is triethylamine, tri-n-butylamine, or N,N-diisopropylethylamine.
[0014] Preferably, the polyether polyol has a molecular weight of 2000-4000 and a functionality of 2-4.
[0015] Preferably, the polyether polyol has a molecular weight of 2000-4000 and a functionality of 3.
[0016] The polyether polyol is a polyoxypropylene polyol.
[0017] Preferably, the catalyst is selected from one or more of dibutyltin dilaurate, stannous octoate, and dibutyltin diacetylacetonate.
[0018] Preferably, the catalyst is dibutyltin dilaurate.
[0019] Preferably, the chain extender is 1,4-butanediol and / or propylene glycol. Preferably, the propylene glycol is 1,2-propanediol or 1,3-propanediol.
[0020] Preferably, the antioxidant is selected from one or more of antioxidant 1010, antioxidant 168 and antioxidant 1076.
[0021] Preferably, the nano-montmorillonite has undergone modification treatment, which includes the following steps: The nano-montmorillonite was ball-milled at a speed of 300-500 rpm, with a ball-to-montmorillonite mass ratio of 10-15:1, for 10-12 hours.
[0022] Preferably, the solvent is selected from one or two of N,N-dimethylformamide, dimethylacetamide, or tetrahydrofuran.
[0023] Preferably, the solvent is N,N-dimethylformamide.
[0024] Technical Theme Two The present invention also provides a method for preparing the above-mentioned high-frequency, high-damping, low-compression-stress polyurethane, comprising the following steps: Mix polyether polyol, damping agent and chain extender, add nano montmorillonite and antioxidant at 60-70℃, disperse by ultrasonication and stir initially, add catalyst and stir again, then add isocyanate and stir for 1-2 minutes. Pour the mixture into a mold and pre-cur at 80-90℃ for 2-3 hours, then heat to 100-120℃ for 4-5 hours. After demolding, leave at room temperature for 6-8 days to obtain the final product.
[0025] Preferably, the ultrasonic dispersion power is 300-400W and the time is 8-12min.
[0026] Preferably, the initial stirring speed and the second stirring speed are both 1500-2000 rpm, and the time is 8-12 min; the final stirring speed is 2000-2500 rpm.
[0027] Technical Theme 3 The present invention also provides the use of high-frequency, high-damping, low-compression-permanent polyurethane as described in Technical Subject 1 in the preparation of pads.
[0028] Preferably, the pad is used in railway lines, bridges and turnouts.
[0029] The beneficial effects of the present invention using the above technical solution are as follows: 1. In this invention, by introducing a damping agent to synergistically mix with an isocyanate system, the high frequency, high damping and low compression set of polyurethane materials are simultaneously improved. At the same time, it also has certain flame retardant properties. The railway pads prepared using this invention have excellent vibration reduction, noise reduction and rail abrasion suppression effects, and significantly extend the service life of the rails.
[0030] 2. The preparation of the damping agent of the present invention consists of two steps: Step 1: First, in the presence of a solvent, 4-chloro-3-methylphenol and an acid-binding agent are mixed and kept at 0-5℃ for 18-22 min. Then, dimethyl phosphite is added dropwise. After the addition is complete, the temperature is raised to 50-70℃ and the reaction is carried out for 2.5-3.5 h to obtain a phosphorus-containing aromatic intermediate. Step 2: Then, 2-chloroethylamine is added to the reaction system, the temperature is raised to 80-90℃, and the reaction is continued for 5-6 h. After the reaction is completed, the product is allowed to stand to precipitate, filtered, washed, and dried to obtain the damping agent.
[0031] The damping agent of this invention has the following structural formula: The reaction formula for step 1 is as follows: The reaction formula for step 2 is as follows: It should be noted that the above reaction formula represents the main reaction pathway and target molecular structure. In actual preparation, the resulting damping agent product is a mixture mainly composed of this target structure. This mixture can also achieve the purpose of this invention and falls within the protection scope of this invention. Those skilled in the art can repeatedly obtain damping agent products possessing the flame-retardant, compression-resistant, and damping properties required by this invention through the described preparation method. The protection scope of this invention is not limited to 100% pure target molecules, but mainly covers the reaction products mainly composed of the target structure and their application in polyurethane preparation. Attached Figure Description
[0032] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0033] Figure 1 The image shows the ¹H NMR spectrum of the damping agent prepared in Example 2 of this invention.
[0034] Figure 2 The damping agent prepared in Example 2 of this invention 13 C NMR spectrum.
[0035] Figure 3 This paper presents a comparative test on rail corrugation of the conventional DT-II type pad of the present invention and the DT-II type pad prepared in Example 2 as rail pads. Figure A shows the rail corrugation after 60 days of laying the conventional DT-II type pad; Figure B shows the rail corrugation after 60 days of laying the DT-II type pad prepared in Example 2.
[0036] Figure 4 This paper presents a comparative test on rail corrugation when the DT-II type pad prepared in Example 2 of the present invention is used as the rail underlayment to replace the conventional DT-II type pad. Figure A shows the rail corrugation state of the section without rail grinding when the existing conventional DT-II type pad is used as the rail underlayment; Figure B shows the rail state after the rail in Figure A has been ground smooth; Figure C shows the rail corrugation state when the conventional DT-II type pad is replaced with the DT-II type pad of Example 2. Detailed Implementation
[0037] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. Unless otherwise specified, the experimental or testing methods involved in the embodiments of this invention are conventional methods in the prior art, and their names and / or abbreviations are conventional names in the art, clearly defined in their respective fields of application. Those skilled in the art can understand the conventional process steps based on these names and apply the corresponding equipment, implementing them under conventional conditions or conditions recommended by the manufacturer. The various instruments, equipment, raw materials, or reagents used in the embodiments of this invention are not subject to any special restrictions on their source; they are all conventional products that can be purchased through legitimate commercial channels and can be prepared according to conventional methods well known to those skilled in the art.
[0039] The raw materials used in the following examples and comparative examples were purchased from the following sources: 4-Chloro-3-methylphenol was purchased from Wuhan Jiyesheng Chemical Co., Ltd. N,N-Dimethylformamide was purchased from Luxi Chemical Group Co., Ltd. Dimethyl phosphite was purchased from Shandong Qizhuo New Material Technology Co., Ltd. 2-Chloroethylamine was purchased from Wuhan Haorong Biotechnology Co., Ltd. Triethylamine was purchased from Jinan Hongyuan Chemical Co., Ltd. The polyether polyol was purchased from Dow Chemical 3003LM, with a molecular weight of 3000 and a functionality of 3. MDI and HDI were purchased from Wanhua MDI-100 and Mitsui Chemicals Takenate 700 in Japan, respectively. Dibutyltin dilaurate was purchased from Changzhou Kerry Chemical Technology Co., Ltd. Antioxidant 1010 was purchased from BASF's Irganox 1010. Nano-montmorillonite was purchased from DK10 produced by Zhejiang Fenghong New Material Co., Ltd. or GK-3 purchased from Jiangxi Gukang New Material Co., Ltd. (DK10 was used in both examples and comparative examples). In this invention, the isocyanate index refers to the ratio of the total number of moles of NCO groups in the actual isocyanate component to the total number of moles of all active hydrogen groups that can react with NCO in the polyol component (i.e., hydroxyl-OH from polyether polyol and chain extender, and amino-NH2 from damper). The hydroxyl content and isocyanate content can be determined according to methods well known to those skilled in the art, or can be theoretically calculated based on the molar ratio of the raw materials. Each damper molecule provides one active hydrogen that can react with NCO.
[0040] Example 1 A high-frequency, high-damping, low-compression-permanent polyurethane is formulated from a polyol component and an isocyanate component in a ratio of 1.1 to an isocyanate index. The polyol component, by mass fraction, includes: 70 parts polyether polyol, 20 parts chain extender 1,4-butanediol, 20 parts damping agent, 5 parts nano montmorillonite, 0.05 parts catalyst dibutyltin dilaurate, and 1 part antioxidant 1010. The isocyanate component is a mixture of 4,4'-diphenylmethane diisocyanate and hexamethylene diisocyanate in a mass ratio of 3:1; the nano-montmorillonite is modified by the following steps: ball milling the nano-montmorillonite at a speed of 400 rpm, with a mass ratio of grinding balls to montmorillonite of 12:1, for 10 hours.
[0041] The method for preparing the damping agent includes the following steps: First, 4-chloro-3-methylphenol and N,N-dimethylformamide were added to a three-necked flask and stirred until dissolved. Triethylamine was then added, and the mixture was cooled to 0°C in an ice-water bath and maintained for 20 minutes. Next, dimethyl phosphite was added dropwise. After the addition was complete, the temperature was raised to 65°C and the reaction proceeded for 3 hours. Then, 2-chloroethylamine was added to the reaction system, and the temperature was raised to 80°C, and the reaction continued for 5 hours. After the reaction was complete, the product was poured into ice water, allowed to stand to precipitate, filtered, washed four times with deionized water, and dried in a vacuum drying oven at 60°C for 12 hours to obtain the damping agent. The molar ratio of 4-chloro-3-methylphenol, triethylamine, dimethyl phosphite, and 2-chloroethylamine was 10:8:8:10; the ratio of 4-chloro-3-methylphenol to N,N-dimethylformamide was 1 g:10 ml.
[0042] The preparation method of the above-mentioned high-frequency, high-damping, low-compression-stress polyurethane includes the following steps: Polyether polyol, damping agent and chain extender are added to the reactor and vacuum dehydrated to a moisture content of ≤0.05%. The temperature is lowered to 60°C, nano-montmorillonite and antioxidant are added, and the mixture is ultrasonically dispersed (300W, 10min) and initially stirred (1800rpm, 10min). Then, catalyst is added and stirred again (1800rpm, 10min). Finally, isocyanate is added and stirred (2200rpm) for 1 minute. The mixture is poured into a mold and pre-cured at 85°C for 2 hours. Then, the temperature is raised to 120°C and cured for 4 hours. After demolding, the mixture is left at room temperature for 7 days to obtain the final product.
[0043] Example 2 A high-frequency, high-damping, low-compression-permanent polyurethane is formulated from a polyol component and an isocyanate component in a ratio of 1.05 to an isocyanate index. The polyol component, by mass fraction, includes: 70 parts polyether polyol, 20 parts chain extender 1,4-butanediol, 20 parts damping agent, 5 parts nano montmorillonite, 0.05 parts catalyst stannous octoate, and 1 part antioxidant 168. The isocyanate component is a mixture of 4,4'-diphenylmethane diisocyanate and hexamethylene diisocyanate in a mass ratio of 3:1; the nano-montmorillonite is modified by the following steps: ball milling the nano-montmorillonite at a speed of 300 rpm, with a mass ratio of grinding balls to montmorillonite of 15:1, for 12 hours.
[0044] The method for preparing the damping agent includes the following steps: First, 4-chloro-3-methylphenol and N,N-dimethylformamide were added to a three-necked flask and stirred until dissolved. Triethylamine was then added, and the mixture was cooled to 0°C in an ice-water bath and maintained for 20 minutes. Next, dimethyl phosphite was added dropwise. After the addition was complete, the temperature was raised to 65°C and the reaction proceeded for 3 hours. Then, 2-chloroethylamine was added to the reaction system, and the temperature was raised to 80°C, and the reaction continued for 5 hours. After the reaction was complete, the product was poured into ice water, allowed to stand to precipitate, filtered, washed four times with deionized water, and dried in a vacuum drying oven at 60°C for 12 hours to obtain the damping agent. The molar ratio of 4-chloro-3-methylphenol, triethylamine, dimethyl phosphite, and 2-chloroethylamine was 10:10:10:12; the ratio of 4-chloro-3-methylphenol to N,N-dimethylformamide was 1 g: 8 ml.
[0045] The obtained damping agent was subjected to ¹H NMR testing, such as... Figure 1As can be seen, the multiplets in the ¹H NMR spectrum at 6.85–7.30 ppm belong to the hydrogen atom signal on the substituted aromatic ring; the singlet at 2.30 ppm corresponds to the methyl proton signal on the aromatic ring; the multiplets in the 4.15–3.85 ppm region can be attributed to the methylene proton bonded to the phosphorus atom; the signal at 3.80–3.60 ppm belongs to the methoxy proton in the phosphate ester structure; the signal at 3.20–2.70 ppm belongs to the methylene proton in the ethyleneamine chain; and the broad peak at 1.50–1.00 ppm is the amino proton signal. These ¹H NMR signals are consistent with the structural characteristics of the target compound, indicating that the reaction successfully generated the target compound. Weak impurity peaks can be observed in some chemical shift regions of the spectrum, presumably originating from small amounts of unreacted reactants or byproducts, but this does not affect the confirmation of the target product's structure. The obtained damping agent was analyzed by ¹³C NMR, such as... Figure 2 As can be seen, the signals in the ¹³C NMR spectrum at 150-145 ppm belong to the quaternary carbon of the aromatic ring bonded to an oxygen atom; the signal at 138-135 ppm belongs to the quaternary carbon of the aromatic ring bonded to a chlorine substituent; multiple signals appear in the 130-115 ppm region, corresponding to the methylene carbon atom on the aromatic ring; the signal at 63-61 ppm belongs to the methoxy carbon in the phosphate ester structure; the signal at 55-52 ppm belongs to the methylene carbon directly bonded to a phosphorus atom; the signal at 41-38 ppm belongs to the methylene carbon in the ethylene amine chain; and the signal at 21-19 ppm corresponds to the methyl carbon of the aromatic ring. These ¹³C NMR signals are consistent with the carbon skeleton structure of the target compound, further proving that the reaction successfully generated the target compound. Weak impurity peaks can be observed in some chemical shift regions of the spectrum, presumably originating from a small amount of unreacted reactants or byproducts, but this does not affect the confirmation of the target product structure. The preparation method of the above-mentioned high-frequency, high-damping, low-compression-stress polyurethane includes the following steps: Polyether polyol, damping agent and chain extender are added to the reactor and vacuum dehydrated to a moisture content of ≤0.05%. The temperature is lowered to 70°C, nano-montmorillonite and antioxidant are added, and the mixture is ultrasonically dispersed (300W, 10min) and initially stirred (1800rpm, 10min). Then, catalyst is added and stirred again (1800rpm, 10min). Finally, isocyanate is added and stirred (2200rpm) for 1 minute. The mixture is poured into a mold and pre-cured at 80°C for 2 hours. Then, the temperature is raised to 110°C and cured for 4 hours. After demolding, the mixture is left at room temperature for 6 days to obtain the final product.
[0046] Example 3 A high-frequency, high-damping, low-compression-permanent polyurethane is formulated from a polyol component and an isocyanate component in a ratio of 1.12 to an isocyanate index. The polyol component, by mass fraction, includes: 70 parts polyether polyol, 25 parts chain extender 1,4-butanediol, 15 parts damping agent, 5 parts nano montmorillonite, 0.05 parts catalyst dibutyltin dilaurate, and 1 part antioxidant 1010. The isocyanate component is a mixture of 4,4'-diphenylmethane diisocyanate and hexamethylene diisocyanate in a mass ratio of 2.8:1; the nano-montmorillonite is modified by the following steps: ball milling the nano-montmorillonite at a speed of 400 rpm, with a mass ratio of grinding balls to montmorillonite of 12:1, for 10 hours.
[0047] The method for preparing the damping agent includes the following steps: First, 4-chloro-3-methylphenol and N,N-dimethylformamide were added to a three-necked flask and stirred until dissolved. Triethylamine was then added, and the mixture was cooled to 5°C in an ice-water bath and maintained for 18 minutes. Dimethyl phosphite was then added dropwise. After the addition was complete, the temperature was raised to 65°C and the reaction proceeded for 3 hours. Next, 2-chloroethylamine was added to the reaction system, and the temperature was raised to 80°C. The reaction continued for 5 hours. After the reaction was complete, the product was poured into ice water, allowed to stand to precipitate, filtered, washed four times with deionized water, and dried in a vacuum drying oven at 60°C for 12 hours to obtain the damping agent. The molar ratio of 4-chloro-3-methylphenol, triethylamine, dimethyl phosphite, and 2-chloroethylamine was 12:6:6:12; the ratio of 4-chloro-3-methylphenol to N,N-dimethylformamide was 1 g:10 ml.
[0048] The preparation method of the above-mentioned high-frequency, high-damping, low-compression-stress polyurethane includes the following steps: Polyether polyol, damping agent and chain extender are added to the reactor and vacuum dehydrated to a moisture content of ≤0.05%. The temperature is then lowered to 70°C, nano-montmorillonite and antioxidant are added, and the mixture is ultrasonically dispersed (400W, 8min) and initially stirred (2000rpm, 8min). Then, catalyst is added and stirred again (2000rpm, 8min). Finally, isocyanate is added and stirred (2500rpm) for 2 minutes. The mixture is poured into a mold and pre-cured at 80°C for 3h. Then, the temperature is raised to 110°C and cured for 5h. After demolding, the mixture is left at room temperature for 7 days to obtain the final product.
[0049] Example 4 A high-frequency, high-damping, low-compression-permanent polyurethane is formulated from a polyol component and an isocyanate component in a ratio of 1.15 to an isocyanate index. The polyol component, by mass fraction, includes: 70 parts polyether polyol, 15 parts chain extender 1,2-propanediol, 25 parts damping agent, 5 parts nano montmorillonite, 0.05 parts catalyst dibutyltin dilaurate, and 1 part antioxidant 168. The isocyanate component is a mixture of 4,4'-diphenylmethane diisocyanate and hexamethylene diisocyanate in a mass ratio of 2.5:1; the nano-montmorillonite is modified by the following steps: ball milling the nano-montmorillonite at a speed of 400 rpm, with a mass ratio of grinding balls to montmorillonite of 12:1, for 10 hours.
[0050] The method for preparing the damping agent includes the following steps: First, 4-chloro-3-methylphenol and N,N-dimethylformamide were added to a three-necked flask and stirred until dissolved. Triethylamine was then added, and the mixture was cooled to 5°C in an ice-water bath and maintained for 18 minutes. Dimethyl phosphite was then added dropwise. After the addition was complete, the temperature was raised to 65°C and the reaction proceeded for 3 hours. Next, 2-chloroethylamine was added to the reaction system, and the temperature was raised to 80°C. The reaction continued for 5 hours. After the reaction was complete, the product was poured into ice water, allowed to stand to precipitate, filtered, washed four times with deionized water, and dried in a vacuum drying oven at 60°C for 12 hours to obtain the damping agent. The molar ratio of 4-chloro-3-methylphenol, triethylamine, dimethyl phosphite, and 2-chloroethylamine was 12:6:6:12; the ratio of 4-chloro-3-methylphenol to N,N-dimethylformamide was 1 g:10 ml.
[0051] The preparation method of the above-mentioned high-frequency, high-damping, low-compression-stress polyurethane includes the following steps: Polyether polyol, damping agent and chain extender are added to the reactor and vacuum dehydrated to a moisture content of ≤0.05%. The temperature is then lowered to 70°C, nano-montmorillonite and antioxidant are added, and the mixture is ultrasonically dispersed (400W, 8min) and initially stirred (2000rpm, 8min). Then, catalyst is added and stirred again (2000rpm, 8min). Finally, isocyanate is added and stirred (2500rpm) for 2 minutes. The mixture is poured into a mold and pre-cured at 90°C for 2 hours. Then, the temperature is raised to 120°C and cured for 4 hours. After demolding, the mixture is left at room temperature for 7 days to obtain the final product.
[0052] Example 5 A high-frequency, high-damping, low-compression-permanent polyurethane is formulated from a polyol component and an isocyanate component in a ratio of 1.15 to an isocyanate index. The polyol component, by mass fraction, includes: 60 parts polyether polyol, 25 parts chain extender 1,2-propanediol, 20 parts damping agent, 3 parts nano-montmorillonite, 0.08 parts catalyst dibutyltin diacetylacetonate, and 0.5 parts antioxidant 1076. The isocyanate component is a mixture of 4,4'-diphenylmethane diisocyanate and hexamethylene diisocyanate in a mass ratio of 3:1; the nano-montmorillonite is modified by the following steps: ball milling the nano-montmorillonite at a speed of 400 rpm, with a mass ratio of grinding balls to montmorillonite of 12:1, for 10 hours.
[0053] The method for preparing the damping agent includes the following steps: First, 4-chloro-3-methylphenol and N,N-dimethylformamide were added to a three-necked flask and stirred until dissolved. Triethylamine was then added, and the mixture was cooled to 5°C in an ice-water bath and maintained for 18 minutes. Dimethyl phosphite was then added dropwise. After the addition was complete, the temperature was raised to 50°C and the reaction proceeded for 3.5 hours. Next, 2-chloroethylamine was added to the reaction system, and the temperature was raised to 80°C. The reaction continued for 6 hours. After the reaction was complete, the product was poured into ice water, allowed to stand to precipitate, filtered, washed four times with deionized water, and dried in a vacuum drying oven at 60°C for 12 hours to obtain the damping agent. The molar ratio of 4-chloro-3-methylphenol, triethylamine, dimethyl phosphite, and 2-chloroethylamine was 10:5:5:10; the ratio of 4-chloro-3-methylphenol to N,N-dimethylformamide was 1 g:12 ml.
[0054] The preparation method of the above-mentioned high-frequency, high-damping, low-compression-stress polyurethane includes the following steps: Polyether polyol, damping agent and chain extender are added to the reactor and vacuum dehydrated to a moisture content of ≤0.05%. The temperature is then lowered to 70°C, nano-montmorillonite and antioxidant are added, and the mixture is ultrasonically dispersed (400W, 8min) and initially stirred (2000rpm, 8min). Then, catalyst is added and stirred again (2000rpm, 8min). Finally, isocyanate is added and stirred (2500rpm) for 2 minutes. The mixture is poured into a mold and pre-cured at 85°C for 2 hours. Then, the temperature is raised to 110°C and cured for 4 hours. After demolding, the mixture is left at room temperature for 8 days to obtain the final product.
[0055] Example 6 The only difference from Example 2 is the addition of unmodified nano-montmorillonite.
[0056] Comparative Example 1 Compared to Example 1, the only difference is that 2-chloroethylamine is replaced with 3-chloropropylamine in the preparation of the damping agent. The preparation method of the damping agent includes the following steps: First, 4-chloro-3-methylphenol and N,N-dimethylformamide were added to a three-necked flask and stirred until dissolved. Triethylamine was then added, and the mixture was cooled to 0°C in an ice-water bath and maintained for 20 minutes. Dimethyl phosphite was then added dropwise. After the addition was complete, the temperature was raised to 65°C and the reaction proceeded for 3 hours. Next, 3-chloropropylamine was added to the reaction system, and the temperature was raised to 80°C. The reaction continued for 5 hours. After the reaction was complete, the product was poured into ice water, allowed to stand to precipitate, filtered, washed four times with deionized water, and dried in a vacuum drying oven at 60°C for 12 hours to obtain the damping agent. The molar ratio of 4-chloro-3-methylphenol, triethylamine, dimethyl phosphite, and 3-chloropropylamine was 10:8:8:10; the ratio of 4-chloro-3-methylphenol to N,N-dimethylformamide was 1 g:10 ml.
[0057] Comparative Example 2 Compared with Example 1, the only difference is that in the preparation of the damping agent, 4-chloro-3-methylphenol is replaced with 2-chloro-4-methylphenol. The preparation method of the damping agent includes the following steps: First, 2-chloro-4-methylphenol and N,N-dimethylformamide were added to a three-necked flask and stirred until dissolved. Triethylamine was then added, and the mixture was cooled to 0°C in an ice-water bath and maintained for 20 minutes. Next, dimethyl phosphite was added dropwise. After the addition was complete, the temperature was raised to 65°C and the reaction proceeded for 3 hours. Then, 2-chloroethylamine was added to the reaction system, and the temperature was raised to 80°C, and the reaction continued for 5 hours. After the reaction was complete, the product was poured into ice water, allowed to stand to precipitate, filtered, washed four times with deionized water, and dried in a vacuum drying oven at 60°C for 12 hours to obtain the damping agent. The molar ratio of 2-chloro-4-methylphenol, triethylamine, dimethyl phosphite, and 2-chloroethylamine was 10:8:8:10; the ratio of 4-chloro-3-methylphenol to N,N-dimethylformamide was 1 g:10 ml.
[0058] Comparative Example 3 Compared to Example 2, the only difference is that no damping agent was used. Specifically, the polyurethane was formulated from polyol components and isocyanate components in a ratio of 1.1 to an isocyanate index. The polyol component, by mass fraction, includes: 70 parts polyether polyol, 20 parts chain extender 1,4-butanediol, 5 parts nano montmorillonite, 0.05 parts catalyst dibutyltin dilaurate, and 1 part antioxidant 1010. The isocyanate component is a mixture of 4,4'-diphenylmethane diisocyanate and hexamethylene diisocyanate in a mass ratio of 3:1; the nano-montmorillonite is modified by the following steps: ball milling the nano-montmorillonite at a speed of 400 rpm, with a mass ratio of grinding balls to montmorillonite of 12:1, for 10 hours.
[0059] The preparation method of polyurethane includes the following steps: Polyether polyol and chain extender are added to a reactor and vacuum dehydrated until the moisture content is ≤0.05%. The temperature is lowered to 60°C, nano-montmorillonite and antioxidant are added, and the mixture is ultrasonically dispersed (300W, 10min) and initially stirred (1800rpm, 10min). Then, catalyst is added and stirred again (1800rpm, 10min). Finally, isocyanate is added and stirred (2200rpm) for 1 minute. The mixture is poured into a mold and pre-cured at 85°C for 2 hours. Then, the temperature is raised to 120°C and cured for 4 hours. After demolding, the mixture is left at room temperature for 7 days to obtain the final product.
[0060] Comparative Example 4 The only difference from Example 3 is that the isocyanate component is a mixture of 4,4'-diphenylmethane diisocyanate and hexamethylene diisocyanate in a mass ratio of 2.3:1.
[0061] Comparative Example 5 Compared with Example 3, the only difference is that the isocyanate component is a mixture of 4,4'-diphenylmethane diisocyanate and hexamethylene diisocyanate in a mass ratio of 3.2:1.
[0062] Test case The materials prepared in the above embodiments and comparative examples were subjected to performance tests, and the results are shown in Tables 1-2. The test methods are as follows: (1) Tensile test at room temperature (GB / T 1040.2-2022); (2) The micro combustion calorimetry test (ASTM D7309-2007a) was conducted using an MCC-2 micro calorimeter; (3) Vertical burning test (ISO 9773-2024), using CZF-6 vertical burning tester; (4) Dynamic mechanical property testing: The damping performance of polyurethane samples was analyzed using a TA-Q800 dynamic mechanical thermomechanical analyzer within a test temperature range of -80 to 100°C. The test mode was uniaxial tension, the test frequency was 1 Hz, and the test heating rate was 3°C / min. The test results are shown in Table 1.
[0063] (5) Determination of permanent compression deformation (GB / T 10653-2001); All samples were placed in an oven at 70℃ and subjected to compression deformation test after 22 hours to test the permanent deformation of the samples.
[0064] (6) The loss factor was evaluated according to the laboratory evaluation method of track vibration reduction effect in T / CCTAS 76 2023.
[0065] (7) The dynamic-to-static stiffness ratio shall be determined according to the method described in TB / T 3395.1.
[0066] Table 1 Table 2 Application Test Example 1 Test Sample 1: The DT-II type pad was obtained using the method of Example 3.
[0067] Test sample 2: The DT-II type pad was obtained using the method of Example 2.
[0068] Test comparison sample 1: The raw materials are prepared by mixing polyol components and isocyanate components in a ratio of 1.1 isocyanate index. By mass, the polyol components include: 66 parts PTMEG-2000, 16 parts LE210, 13 parts LE310, 6 parts BDO, 0.03 parts dibutyltin dilaurate (T12), 0.3 parts stannous octoate (T9), and 0.5 parts antioxidant 168. The isocyanate component is WANNATE® 3W6698 isocyanate prepolymer. Preparation method: The polyol components and isocyanate components are mixed and reacted at a speed of 6000 r / min. The mixture is poured into a mold, cured at 80°C for 7 minutes, demolded, and the prepared product is cured at 100°C for 24 hours to obtain a conventional DT-II type pad.
[0069] Test comparison sample 2: The raw materials are prepared by mixing polyol components and isocyanate components in a ratio of 1.1 isocyanate index. By mass, the polyol components include: 70 parts PTMEG-2000, 9 parts LE220, 13 parts LE310, 8 parts NPG, 0.02 parts dibutyltin dilaurate (T12), 0.35 parts stannous octoate (T9), and 1.0 part antioxidant 1010. The isocyanate component is the isocyanate prepolymer WANNATE® 3W6698. Preparation method: The polyol components and isocyanate components are mixed and reacted at a speed of 6000 r / min. The mixture is poured into a mold, cured at 80°C for 7 minutes, demolded, and the prepared product is cured at 100°C for 24 hours to obtain the conventional DT-II type pad.
[0070] The raw material indicators for test comparison sample 1 and test comparison sample 2 are as follows: Polyether polyol PTMEG-2000, functionality 2, molecular weight 2000, hydroxyl value 56; Polyether polyol LE210, purchased from Shandong Longhua New Material Co., Ltd., has a functionality of 2, a molecular weight of 1000, and a hydroxyl value of 112. Polyether polyol LE310, purchased from Shandong Longhua New Material Co., Ltd., has a functionality of 3, a molecular weight of 1000, and a hydroxyl value of 168. Polyether polyol LE220, purchased from Shandong Longhua New Material Co., Ltd., has a functionality of 2, a molecular weight of 2000, and a hydroxyl value of 56. WANNATE® 3W6698 is an MDI-PTMG prepolymer purchased from Wanhua Chemical Group Co., Ltd., with an isocyanate content of 12%.
[0071] The tests were conducted using an electro-hydraulic servo testing machine and a high-frequency dynamic stiffness testing device. The test included the static stiffness, dynamic stiffness (4Hz), high-frequency dynamic stiffness (20Hz~200Hz), and loss factor of the aforementioned pad. The static stiffness and dynamic stiffness (4Hz) were measured according to standard TB / T 3395.1, and the high-frequency dynamic stiffness (20Hz~200Hz) and loss factor were measured according to the laboratory evaluation method for track vibration reduction effect (T / CCTAS 76―2023). The results are shown in Table 3-4.
[0072] Table 3 Table 4 Application Test Example 2 Test sample 2: DT-II type pad obtained using the method of Example 2.
[0073] Comparative Sample 2: The raw materials and preparation methods are the same as those in Comparative Sample 2 of Application Test Example 1, resulting in a conventional DT-II type pad.
[0074] A section with a curve radius of 400 m was selected on the same subway line as a test track. First, the rails in this section were ground. Then, a comparative test was conducted using conventional DT-II type shims and the DT-II type shims prepared in Example 2 as rail pads. The rail corrugation condition was observed and analyzed 60 days after laying. Figure 3 As shown, Figure 3 In the diagram, A represents the rail corrugation condition 60 days after laying the existing conventional DT-II type pad; B represents the rail corrugation condition 60 days after laying the DT-II type pad prepared in Example 2. Comparing the corrugation development trends, it can be seen that after using the DT-II type pad of Example 2, a stable contact light band was formed between the wheel and rail, and the rail corrugation did not develop further.
[0075] A section with a curve radius of 400 m was selected on the same subway line as a test paving section, such as... Figure 4 As shown, Figure 4 In section A, the text indicates the corrugated state of the rails in a section where existing conventional DT-II type rail pads were laid as rail supports without prior rail grinding. The rails were subsequently ground smooth. Figure 4 As shown in Figure B. Following this, the conventional DT-II type pad in this section was replaced with the DT-II type pad of Example 2, and a comparative test was conducted before and after the replacement. The results are as follows... Figure 4 As shown in Figure C, after 60 days of replacing the DT-II type pad of Example 2, the original corrugation of the rail was reduced due to the change in the wheel-rail interaction relationship, and the upper corrugation was gradually suppressed.
[0076] Application Test Example 3 Test sample 3: DT-III type pad obtained using the method of Example 2.
[0077] Test Comparison Sample 3: The raw materials and preparation methods are the same as those of Test Comparison Sample 2 in Application Test Example 1, and a conventional DT-III type pad is prepared.
[0078] In subway lines, the rail surface is first subjected to standardized grinding as a pretreatment process. Then, DT-III type shims prepared in Example 2 and conventional DT-III type shims are laid as rail underlayment for comparison in the corresponding track sections. The minimum curve radius of the trial laying section is 3000 m, and the rail corrugation condition is observed and measured 50 days after laying. The test results show that using the existing conventional DT-III type shims, the rail corrugation depth is 0.06 mm with a wavelength of 118 mm; while using the DT-III type shims prepared in Example 2, the rail corrugation depth is reduced to 0.02 mm with a wavelength of 123 mm, indicating a smoother corrugation development process and a significant improvement in track surface smoothness. Therefore, the polyurethane pad used in Example 2 has a better vibration reduction effect, which can more effectively absorb the dynamic load and vibration impact generated during train operation, reduce the alternating stress level of the rail, thereby delaying the generation and expansion of rail corrugation, which is conducive to improving the overall stability of track operation, extending the service life of rail, and further reducing track maintenance costs.
[0079] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A polyurethane with high frequency, high damping, and low compression set, characterized in that: It is formulated from a polyol component and an isocyanate component in a ratio of 1.05-1.15; wherein, by mass parts, the polyol component includes: 60-80 parts of polyether polyol, 15-25 parts of chain extender, 15-25 parts of damping agent, 3-8 parts of nano-montmorillonite, 0.03-0.08 parts of catalyst, and 0.5-1.5 parts of antioxidant; the isocyanate component is a mixture of 4,4'-diphenylmethane diisocyanate and hexamethylene diisocyanate in a mass ratio of 2.5-3:
1. The method for preparing the damping agent includes the following steps: in the presence of an acid-binding agent and a solvent, 4-chloro-3-methylphenol is reacted with dimethyl phosphite to generate a phosphorus-containing aromatic intermediate, which is then subjected to a nucleophilic substitution reaction with 2-chloroethylamine, and the damping agent is obtained after post-treatment; the molar ratio of 4-chloro-3-methylphenol, dimethyl phosphite and 2-chloroethylamine is 8-12:5-10:10-12.
2. The high-frequency, high-damping, low-compression-permanent polyurethane according to claim 1, characterized in that, The preparation method of the damping agent includes the following steps: 4-chloro-3-methylphenol and an acid-binding agent are mixed in the presence of a solvent and kept at 0-5℃ for 18-22 min. Then, dimethyl phosphite is added dropwise. After the addition is complete, the temperature is raised to 50-70℃ and reacted for 2.5-3.5 h. Then, 2-chloroethylamine is added to the reaction system, the temperature is raised to 80-90℃, and the reaction is continued for 5-6 h. After the reaction is completed, the damping agent is obtained through post-treatment.
3. The high-frequency, high-damping, low-compression-permanent polyurethane according to claim 1, characterized in that, The polyether polyol is a polyoxypropylene polyol with a molecular weight of 2000-4000 and a functionality of 2-4.
4. The high-frequency, high-damping, low-compression-permanent polyurethane according to claim 1, characterized in that, The catalyst is selected from one or more of dibutyltin dilaurate, stannous octoate, and dibutyltin diacetylacetonate.
5. The high-frequency, high-damping, low-compression-permanent polyurethane according to claim 1, characterized in that, The antioxidant is selected from one or more of antioxidant 1010, antioxidant 168 and antioxidant 1076.
6. The high-frequency, high-damping, low-compression-permanent polyurethane according to claim 1, characterized in that, The nano-montmorillonite is modified by the following steps: ball milling the nano-montmorillonite at a speed of 300-500 rpm, with a mass ratio of grinding balls to montmorillonite of 10-15:1, for 10-12 hours.
7. The high-frequency, high-damping, low-compression-permanent polyurethane according to claim 1, characterized in that, The solvent is selected from one or two of N,N-dimethylformamide, dimethylacetamide, or tetrahydrofuran.
8. The method for preparing high-frequency, high-damping, low-compression-stress polyurethane according to any one of claims 1-7, characterized in that, Includes the following steps: Mix polyether polyol, damping agent and chain extender, add nano montmorillonite and antioxidant at 60-70℃, disperse by ultrasonication and stir initially, add catalyst and stir again, then add isocyanate and stir for 1-2 minutes. Pour the mixture into a mold and pre-cur at 80-90℃ for 2-3 hours, then heat to 100-120℃ for 4-5 hours. After demolding, leave at room temperature for 6-8 days to obtain the final product.
9. Use of the polyurethane as described in any one of claims 1-7 in the preparation of pads.
10. The use according to claim 9, characterized in that, The pads are used in railway lines, bridges, and turnouts.
Citation Information
Patent Citations
High-static-rigidity high-damping low-pressure-change polyurethane elastomer and preparation method thereof
CN120535721A
High-damping polyurethane elastic material and preparation method thereof
CN109824845A
High-damping anti-fatigue and anti-aging polyurethane elastomer and preparation method thereof
CN119409937A